PENERAPAN METODE LEARNING STARTS WITH A QUESTION UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN FIQH KELAS VIII A - Sri Wahyumi; Johan Andriesgo; Ikrima Mailani (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
The low motivation of student learning in fiqh subjects in class VIII A at MTs TI Koto Lubuk Jambi, Kuantan Mudik District, which is marked by pre-research results that show the lack of enthusiasm of students in learning and teachers have not used varied learning methods, so researchers want to conduct classroom action research (PTK) in order to see how the teaching and learning process that researchers do goes according to what is expected. This study aims to determine how the application of the Learning starts with a question method in fiqh subjects at Mts TI Koto Lubuk Jambi, Kuantan Mudik District and whether this method can increase learning motivation. The research conducted is Classroom Action Research, to obtain the data needed, this study uses data collection techniques namely observation, interviews and documentation. From this study it can be concluded that the application of the Learning starts with a question method in increasing student motivation in fiqh subjects in class VIII A in Mts TI Koto Lubuk Jambi, Kuantan Mudik Subdistrict, Kuantan Singingi Regency is successful in accordance with the learning plan. This is known from the observations of the observation sheet with the percentage of application reaching 100%. Through the application of the method, it can improve students' motivation in class VIII A in fiqh subjects at MTs TI Koto Lubuk Jambi, Kuantan Mudik District. This is evident from, in pre-action (pre-cycle) only 12.41% of the observations of students' motivation, then in cycle 1 it increased to 35.85, in cycle 2 it again increased to 53.79%, as well as cycle 3 the results of observations of student motivation to become 80.68%.